N. V. Gogol’s Treatment in Ostend and Gräfenberg - E. I. Manyanina (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The article is devoted to Gogol’s therapeutic courses by the North sea in Ostend and in Gräfenberg hydropathic of Dr. Vincent Priessnitz. The research problem is identified as the attempt to assess the effect of the therapy with cold water on mood of the writer on the basis of Gogol’s epistolary heritage and his contemporaries’ memories. Special attention is paid to the historical and cultural context of the journeys of the Russian nobility in the 19th century to Western European resort towns. The memoirs of Gogol’s contemporaries on the thermal therapy are analyzed. A conclusion is made about the impact of thermal treatment on the health and creative spirit of Gogol, how therapy in the Belgian Ostend and Czech Gräfenberg (modern Jeseník ) helped him recover from his prolonged illness. The research urgency is caused by the fact that the theme of Gogol’s stay on “cold” resort in Ostend and at the hydropathic established by Dr. Priessnitz is raised in Gogol studies for the first time and is of interest in the context of the study the biography of the writer and his memorial place names. The results of the study can be applied in the study of the life and works of Gogol, as well as in the teaching on the course of history of Russian literature.